2020
DOI: 10.1038/s41598-020-73893-5
|View full text |Cite
|
Sign up to set email alerts
|

Accurate population estimation of Caprinae using camera traps and distance sampling

Abstract: With most of the world’s Caprinae taxa threatened with extinction, the IUCN appeals to the development of simple and affordable sampling methods that will produce credible abundance and distribution data for helping conserve these species inhabiting remote areas. Traditional sampling approaches, like aerial sampling or mark-capture-recapture, can generate bias by failing to meet sampling assumptions, or by incurring too much cost and logistical burden for most projects to address them. Therefore, we met the IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Considering the robust theoretical framework, specific software and advice for study design, testing CT‐DS could considerably increase the applicability of camera traps for the monitoring of unmarked populations. To date, CT‐DS has been applied in a chimpanzee population (Cappelle et al., 2019), a community of species of the rainforest (Bessone et al., 2020, Cappelle et al, 2021), a bighorn sheep population (Harris et al., 2020) and a marmot population (Corlatti et al., 2020). The REM is, without a doubt, the most applied method (Gilbert et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the robust theoretical framework, specific software and advice for study design, testing CT‐DS could considerably increase the applicability of camera traps for the monitoring of unmarked populations. To date, CT‐DS has been applied in a chimpanzee population (Cappelle et al., 2019), a community of species of the rainforest (Bessone et al., 2020, Cappelle et al, 2021), a bighorn sheep population (Harris et al., 2020) and a marmot population (Corlatti et al., 2020). The REM is, without a doubt, the most applied method (Gilbert et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, CT-DS has been applied in a chimpanzee population (Cappelle et al, 2019), a community of species of the rainforest (Bessone et al, 2020, Cappelle et al, 2021, a bighorn sheep population (Harris et al, 2020) and a marmot population (Corlatti et al, 2020). The REM is, without a doubt, the most applied method (Gilbert et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…But, for wild ungulates which lack distinctive unique markings, camera traps could still be limited to providing an index of relative abundance rather than absolute abundance (Gilbert et al, 2020), much as we have reported here. However, new camera trap methods are emerging which may effectively estimate abundance of unmarked animals, including time-toevent and space-to-event models (Moeller et al, 2018;Loonam et al, 2020), the random encounter and staying time model (Nakashima et al, 2018(Nakashima et al, , 2020, and distance sampling with camera trap images (Howe et al, 2017;Harris et al, 2020); these and other new methods could be explored and trialed in future.…”
Section: Discussionmentioning
confidence: 99%
“…Applied uses include those with the primary aims of describing, characterizing, and monitoring observed phenomena, including species distribution and abundance, animal movements and home ranges, or resource selection (45,78,79). These studies frequently adopt a top-down perspective in which the predominant focus is on groups (e.g., populations), with individuals simply viewed as units within the group, and minimal interpretation of individual variability.…”
Section: Applications Of Animal Identification In Field and Laborator...mentioning
confidence: 99%